I hate summer. It makes me forget things. Like stuff I haven't done since 8th grade. Can someone help me solve this equation? I've been doin it since 3:30 today. And its 5:50 now. Its driving me crazy, this book sucks. It tells you the answer in the back, but not how to get it. The online calculators suck, too. The answer is supposed to be 11/6. Here is the equation -
7/2x+1 - 8x/2x-1 = -4
Im going to burn this book :(
ID:277088
![]() Aug 30 2006, 11:48 am
|
|
There is a minor hitch. 2x+1 is a factor of the quadratic equation you got, which means the two solutions are x=11/16 and x=-1/2, but the latter is one of the denominators of the original equation. Analyzing the original equation as y=7/(2x+1)-8x/(2x-1), you can see there are two vertical asymptotes, one of them at x=1/2 and one at x=-1/2. Hence, we have to throw out the x=-1/2 solution, and x=11/16 is the only answer.
Lummox JR |
Ah, your equation is wrong, too Xx
But I figured it out. Thanks to you, you set me on the right path. That 32 squared isn't supposed to be there. |
Lummox JR wrote:
There is a minor hitch. 2x+1 is a factor of the quadratic equation you got, which means the two solutions are x=11/16 and x=-1/2, but the latter is one of the denominators of the original equation. Analyzing the original equation as y=7/(2x+1)-8x/(2x-1), you can see there are two vertical asymptotes, one of them at x=1/2 and one at x=-1/2. Hence, we have to throw out the x=-1/2 solution, and x=11/16 is the only answer. Even though I didn't understand a thing you said, I figured it out. 11/16 isn't the only answer. Heres what I got - 1) 7/(2x+1) - 8x/(2x-1) = -4 2) (2x-1)7/(2x+1)(2x-1) - (2x+1)8x/(2x-1)(2x+1) = -4(4x^2-1) 3) 14x - 7 -16x^2 -8x = -16x^2 + 4 4) 6x -11 = 0 5) X = 11/6 |
Yeah, I realised it was wrong before yours (and LJR's) post, as I said on wiz_chat
[Aug 31 00:24] DeathAwaitsU: Oh wait [Aug 31 00:24] DeathAwaitsU: I messed up [link] [Aug 31 00:24] DeathAwaitsU: I'll try it by hand instead But you beat me to it =P. |
7/(2x+1) - 8x/(2x-1) = -4
In which case
7(2x+1)(2x-1)/(2x+1) - 8x(2x+1)(2x-1)/(2x-1) = -4(2x+1)(2x-1) //times everything by (2x+1)(2x-1) to get rid of the fractions
(14x-7) - (16x^2+8x) = -4(4x^2-1)
-16x^2 + 6x - 7 = 16x^2 + 4
32x^2 - 6x + 11 = 0
Use the quadratic formula on that to solve.
*Edit*
Made a mistake:
(14x-7) - (16x^2+8x) = -4(4x^2-1)
-16x^2 + 6x - 7 = -16x^2 + 4
6x = 11
x = 11/6